PELAKSANAAN ASAS ITIKAD BAIK DALAM PERJANJIAN KERJASAMA USAHA XAFA GROUP KEBAB TURKI ALA FANDAWA DI KOTA PEKANBARU - MALELA, GITA REGINA; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The cooperation agreement between the owner of capital and the manager of venture capital of Xafa Group Kebab Turki Ala Fandawa is a legally-made agreement to act as a law for the parties making it, in accordance with the principle of